How to account for tax planning and tax uncertainty in valuation: Separate vs. composite view - Jonas Knaisch (Arbeitskreis Quantitative Steuerlehre (arqus), 2022)
I investigate how investors value tax planning and tax uncertainty for the case of publicly listed German firms. I compare two recent approaches how to account for tax uncertainty: the separate view by Drake et al. (2019) and the composite view by Jacob and Schütt (2020) to find the better suited way to incorporate tax planning and uncertainty simultaneously. In a battery of tests, I fail to produce results consistent with the separate view. In contrast, the composite view yields robust results that are in line with theory and prior literature: A one standard deviation increase in the quality of tax planning leads to an increase in the positive effect of the return on equity on the firm value of 7.7%. Investors seem to not only care about the level of firms' tax planning, but also how it is achieved. Only combining the degree of tax planning and its associated uncertainty in a single measure (Tax Planning Score) leads to robust results, thereby providing support for the notion of Jacob and Schütt (2020) that these constructs should be considered jointly.
Keywords: G32; H25; H26; M21; M41; 330; Tax Avoidance; Tax Uncertainty; Firm Value; Tax Planning Score